Prevalence of sexually transmitted infections among young married women in Thiruvarur district of Tamil Nadu state in India - Ravi, Rejoice Puthuchira; Kulasekaran, Ravishankar Athimulam (Indian Journal of Community Health, 2014)
Background: Sexually transmitted infections (STIs) are now recognized as a serious global threat to the health of population. Objectives: To assess the prevalence of sexually transmitted infections among young married scheduled castes women in Thiruvarur district of Tamilnadu state in India. Methods: A community based cross-sectional study was conducted in 28 villages selected using multistage sampling technique for selecting 605 women in the age group of 15-24 years during July 2010-April 2011. Data analysis was by use of SPSS version-17, with statistical significance set at p-value of 0.05. Results: Around 8.8% of women experienced sexually transmitted infections among the study population. The proportion of women who experienced STIs was seven times higher among illiterates (46.9%) than women who completed secondary education (6%). The women in households in the high standard of living index (SLI) were less likely to experience STIs (1.7%) than women in low SLI (15.6%). The agricultural laborers were 1.145 times more likely to experience STIs than non-agricultural workers (OR=0.251). Conclusions: The main causes for sexual health problems were found to be the less education and lowest SLI among women. It is recommended that policy makers should be introduce community intervention programs to increase the awareness regarding sexual health issues among rural population.